Analysis of Influence of Tilt Angle on Variable-Speed Fixed-Pitch Floating Offshore Wind Turbines for Optimizing Power Coefficient Using Experimental and CFD Models - Wisatesajja, Wongsakorn; Roynarin, Wirachai; Intholo, Decha (International Journal of Renewable Energy Development, 2021)
This study focused on optimization of the power coefficient of floating offshore wind turbines (FOWTs) to maintain their wind power performance in order to overcome problems with the tilt angle resulting from an unstable wind turbine platform, which can reduce the effective area of wind turbine energy extraction. FOWTs with a variable-speed fixed-pitch control strategy were investigated using an experimental model in a wind tunnel and a CFD simulation model for analysis and comparison, using wind speeds of 2–5.5 m/s and tilt angles of 3.5–6.1°. The results showed that average rotational speed differences of 16.4% and optimal power coefficients of 0.35–0.36 could be maintained at tip speed ratios of 7.7–9.6 during wind speeds of 3–5 m/s with tilt angles of 3.9–5.8°. The results of this study provide insights into a new concept of power coefficient optimization using variable tilt angle for small to medium fixed pitch FOWTs, to reduce the cost of pitch control systems.